2010 IEEE International Conference on Acoustics, Speech and Signal Processing 2010
DOI: 10.1109/icassp.2010.5495421
|View full text |Cite
|
Sign up to set email alerts
|

Sparse optimization with directional DCT bases for image compression

Abstract: This paper proposes a new compression algorithm based on the directional DCT (DDCT) bases introduced in [1]. We first explain how to extend the DDCT concept to rectangular bases and exploit them to build a set of bases using a bintree segmentation. We then use dynamic programming to select a basis from this set according to a rate-distortion criterion. Comparisons in terms of rate-distortion performance are finally made with the current compression standards JPEG and JPEG2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In [9], [35], [36], it has been shown that for DCT transforms there is an approximately linear relationship between the coding bitrate R c and the 0 -norm of c, that is, the number of its non-zero coefficients, i.e. R c = α c 0 (9) where α can be empirically found [35]. Let us now discuss R θ .…”
Section: A Rd Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In [9], [35], [36], it has been shown that for DCT transforms there is an approximately linear relationship between the coding bitrate R c and the 0 -norm of c, that is, the number of its non-zero coefficients, i.e. R c = α c 0 (9) where α can be empirically found [35]. Let us now discuss R θ .…”
Section: A Rd Modelmentioning
confidence: 99%
“…To overcome this problem, various approaches and solutions have been developed [5], most of which consist in modifications of the 2D-DCT in order to incorporate directional information [3], [6]- [9]. The Directional DCT (DDCT) presented in [3] is the first attempt in this sense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model-based work hence focused on the design of anisotropic transforms (multiresolution transforms such as [8], [33], [35], [45] as well as block-based designs [10], [18], [38], [51]) that were geared toward obtaining substantially better performance over directional singularities. On the data-driven side, noting the suboptimality of principal component analysis (PCA) methods and the KLT [13], researchers have concentrated on "independent" component analysis (ICA) and matching pursuit designs among others [20], [32].…”
Section: Introductionmentioning
confidence: 99%
“…In [7], it is suggested to not apply the secondstage DCT, or to apply it only on the DC coefficients generated during the first transform [8]. In [9], DDCT [3] is improved using anisotropic local basis supports, where the optimal basis is selected exploiting the bintree structure of the dictionary. These methods, however, have several issues.…”
Section: Introductionmentioning
confidence: 99%